Kesenian Singa Manuk Dari Desa Anggasari Kabupaten Subang - Muhammad Luthfi Abdul Aziz; Didin Saripudin (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
This study aims to describe the dynamics of the development of the Singa Manuk art in the village of Anggasari, Subang Regency, from 2003-2015. The author uses historical methods, namely heuristics, criticism, interpretation, and historiography. The research technique uses field studies and literature studies. Based on the results of the study, it was explained that the background of the birth of Singa Manuk art in Anggasari Village was due to a cultural mix between Subang culture through its Sisingaan art and typical Pantura’s dangdut music which was based on the unrest of the artists in Anggasari Village about the dimming of the artistry so that it gave birth to innovations namely Singa Manuk art. Singa Manuk art experienced a dynamic development from 2003 by Sanggar Genades until 2015. Singa Manuk art in Anggasari Village is experiencing continuous development and innovation by artists in the village so that Singa Manuk art continues to be in demand by the community and is preserved. The effort to preserve the Singa Manuk art involves various parties, namely artists, district governments, village governments, and the community who preserve Singa Manuk art.Keywords : Art Preservation, Singa Manuk Art, Subang ArtAbstrakPenelitian ini bertujuan untuk mendeskripsikan dinamika dari perkembangan kesenian Singa Manuk di Desa Anggasari, Kabupaten Subang tahun 2003-2015. Penulis menggunakan metode historis, yaitu heuristik, kritik, interpretasi, dan historiografi. Teknik penelitiannya menggunakan studi lapangan dan studi literatur. Berdasarkan hasil penelitian, dijelaskan bahwa latar belakang lahirnya kesenian Singa Manuk di Desa Anggasari dikarenakan adanya percampuran budaya antara budaya Subang lewat kesenian Sisingaan nya dengan musik dangdut khas Pantura yang didasari oleh keresahan para seniman di Desa Anggasari tentang semakin redupnya kesenian tersebut sehingga melahirkan inovasi baru yaitu kesenian Singa Manuk. Kesenian Singa Manuk mengalami perkembangan yang dinamis, dimulai dari tahun 2003 oleh Sanggar Genades hingga 2015 kesenian Singa Manuk di Desa Anggasari mengalami perkembangan dan inovasi terus-menerus oleh para seniman di desa tersebut, sehingga kesenian Singa Manuk terus diminati oleh masyarakat dan terlestarikan. Upaya pelestarian kesenian Singa Manuk melibatkan berbagai pihak, yaitu para seniman, pemerintah kabupaten, pemerintah desa juga masyarakat yang ikut andil dalam melestarikan kesenian Singa Manuk.Kata kunci : Kesenian Singa Manuk, Kesenian Subang, Pelestarian Kesenian.